2015
DOI: 10.1371/journal.pone.0144437
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Arteriolar Morphometry Based on Full Width at Half Maximum Analysis of Spectral-Domain Optical Coherence Tomography Images

Abstract: ObjectivesIn this study, we develop a microdensitometry method using full width at half maximum (FWHM) analysis of the retinal vascular structure in a spectral-domain optical coherence tomography (SD-OCT) image and present the application of this method in the morphometry of arteriolar changes during hypertension.MethodsTwo raters using manual and FWHM methods measured retinal vessel outer and lumen diameters in SD-OCT images. Inter-rater reproducibility was measured using coefficients of variation (CV), intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(41 reference statements)
2
8
0
Order By: Relevance
“…However, in the subgroup of patients with diabetes duration >60 months ID was similar and WT as well as CA greater compared to healthy individuals, which is consistent with the results obtained in subcutaneous arteriolar vessels [34]. Our findings of hypertrophic remodeling in the subgroup of patients with greater than 60 months diabetes duration are also in accordance with increased retinal WT found in the hypertensive diabetic population in Tong's et al [35] clinical investigation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, in the subgroup of patients with diabetes duration >60 months ID was similar and WT as well as CA greater compared to healthy individuals, which is consistent with the results obtained in subcutaneous arteriolar vessels [34]. Our findings of hypertrophic remodeling in the subgroup of patients with greater than 60 months diabetes duration are also in accordance with increased retinal WT found in the hypertensive diabetic population in Tong's et al [35] clinical investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of hypertrophic remodeling in the subgroup of patients with greater than 60 months diabetes duration are also in accordance with increased retinal WT found in the hypertensive diabetic population in Tong's et al . clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 11 OCT offers high spatial resolution, noninvasive imaging, and high-image acquisition rates, which allows for large field of view and cellular resolution imaging of the morphology of biological tissues. In the past, a number of studies have been conducted to measure the blood vessel caliber from cross-sectional OCT B-scans 12 18 or the shadow profiles of blood vessels. 19 Specifically, Ouyang et al 17 used OCT cross-sectional images for measuring RBVCs in a clinical study, and showed high correlation with data acquired with an infrared reflectance (IR) imaging system.…”
Section: Introductionmentioning
confidence: 99%